First you must distribute the 2x to the numbers inside the parentheses
(2x * x) + (2x * -1) = 3
- 2x = 3
To make this a quadratic equation you can solve bring the 3 over to the left side of the equation by subtracting it to both sides
- 2x - 3 = 0
Use the quadratic equation to solve this (image of the quadratic equation is below)
Remember that quadratic functions are set up like so:
That means that in this equation...
a = 2
b = -2
c = -3
^^^Plug these numbers into the quadratic equation and solve...
Keep in mind that +/- is ±
^^^Exact answers
Approximations:
1.823
-0.823
Hope this helped!
~Just a girl in love with Shawn Mendes